Chemical Design of Palladium‐Based Nanoarchitectures for Catalytic Applications. Issue 6 (11th January 2019) - Iqbal, Muhammad; Kaneti, Yusuf Valentino; Kim, Jeonghun; Yuliarto, Brian; Kang, Yong‐Mook; Bando, Yoshio; Sugahara, Yoshiyuki; Yamauchi, Yusuke
Abstract: Palladium (Pd) plays an important role in numerous catalytic reactions, such as methanol and ethanol oxidation, oxygen reduction, hydrogenation, coupling reactions, and carbon monoxide oxidation. Creating Pd‐based nanoarchitectures with increased active surface sites, higher density of low‐coordinated atoms, and maximized surface coverage for the reactants is important. To address the limitations of pure Pd, various Pd‐based nanoarchitectures, including alloys, intermetallics, and supported Pd nanomaterials, have been fabricated by combining Pd with other elements with similar or higher catalytic activity for many catalytic reactions. Herein, recent advances in the preparation of Pd‐based nanoarchitectures through solution‐phase chemical reduction and electrochemical deposition methods are summarized. Finally, the trend and future outlook in the development of Pd nanocatalysts toward practical catalytic applications are discussed. Abstract : Due to its high catalytic activity, palladium (Pd) has received tremendous attention for many catalytic reactions. Various Pd‐based nanoarchitectures, including alloys, intermetallics, and supported Pd materials, have been synthesized through chemical reduction and electrochemical deposition methods to develop cost‐effective and high‐performance Pd‐based nanocatalysts.